A Low-Cost Method for Understanding How Nature-Based Early Learning and Childcare Impacts Children’s Health and Wellbeing - Traynor, Oliver; Martin, Anne; Johnstone, Avril; Chng, Nai Rui; Kenny, Jessica; McCrorie, Paul (Frontiers in Psychology, 2022)
Nature-based play and learning provision is becoming increasingly popular across the early learning and childcare (ELC) sector in Scotland. However, there remains a lack of understanding of how the program is expected to function. This has implications for program learning and may affect wider rollout of the program. Secondary data analysis of parent interviews (n = 22) and observations (n = 7) in Scottish ELC settings, and review of internationally published studies (n = 33) were triangulated to develop a program theory using the Theory of Change approach. This approach makes a program’s underlying assumptions explicit by systematically demonstrating the relationship between each component: inputs, activities, outcomes, impact, and the contexts of the program. Findings suggested that location of outdoor nature space, affordances, availability of trained practitioners, and transport to location lead to activities such as free play, educator-led activities, and interactions with nature, resulting in longer durations of physical activity, interactions with peers and educators, and increased engagement with the natural environment. These activities are vital for supporting children’s physical, cognitive, social, and emotional development. Our results demonstrate the value of using secondary data analysis to improve our understanding of the underlying theory of nature-based ELC which can support future evaluation designs. These findings will be of interest to program evaluators, researchers, practitioners, and funders, who find themselves with limited resources and want to better understand their program before investing in an evaluation. We encourage researchers and evaluators in the field of early years and outdoor play in other countries to refine this logic model in their own context-specific setting.